Exploring the influencing effect of tertiary teachers’ perceived organizational support and teacher self-efficacy on their job satisfaction: the mediating role of teacher work engagement - Chen, Mei (Frontiers in Psychology, 2025)
Teacher job satisfaction is a central concern within the teaching profession, garnering significant global attention. This research investigates the relationships among perceived organizational support, teacher self-efficacy, work engagement, and job satisfaction among tertiary teachers in Western China. Using a survey methodology, data were collected from 450 teachers at public universities. The findings revealed significant positive correlations among all variables. Crucially, work engagement was found to partially mediate the positive relationship between perceived organizational support and job satisfaction, as well as between teacher self-efficacy and job satisfaction. These results contribute to existing theory by highlighting the pivotal role of work engagement and offer practical insights for enhancing teacher satisfaction. Recommendations are provided for policymakers, administrators, and teacher education programs. The study concludes by suggesting avenues for future research, such as incorporating additional cognitive and non-cognitive factors to deepen the understanding of job satisfaction determinants.